Annual Plan 2000-2001 Volume I Government of Karnataka - Planning Commission (Planning Commission, 2000)
The budgeted outlay for the Annual Plan 2000-2001 is Rs.7274 crores. The budgeted outlay represents an increase of 39 per cent over the revised outlay of 1999-2000 and 24% over the budgeted outlay. The district Plan for 2000-2001 has been fixed at Rs.962.36 crore. This represents an increase of 21.5% over the district plan outlay 1999-2000. The outlay for externally aided projects in 2000-2001 is Rs.754. 5 crores. Under the Special Component Plan Rs.445.26 crores have been earmark 1 for the welfare of Scheduled Castes and Rs.89.67 crores for the Scheduled Tribes under the Tribal SubPlan.
Planning, Institutional Finance and Statistics and Science and Technology Department